The legal Bases of the war of the Global Coalition against the Islamic State in Iraq - Kaka Amin, Zana Tawfeeq; Fatah, Omed Rafiq (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
Terror is considered one of the serious threats to the international community. Responding to these threats is beyond the capabilities of an individual state, so international coalitions are an important tool to counteract the threats of terrorism. The emergence of the Islamic State in Iraq and Syria (ISIS) as terrorist organization has become a major factor to instability of the world peace and security. As a result, the International Coalition has come to existence with the leadership of the United States. The intervention against the ISIS in Iraq has raised a number of legal questions and interpretations. The key question is how to use force against the Islamic State (Terrorist Organization)? Therefore, this study seeks to provide a critical analysis for legal justifications of the U.S. military intervention against ISIS within the international law framework. The research begins with the Security Council Resolution (2249) and the state consent principle (Intervention by Invitation), as well as analysis of the implementation of self and collective defense rights. The study concludes that the use of force against ISIS is legally justified on Iraqi territory.